Strategi penjualan polis asuransi kebakaran Studi kasus: PT. Asuransi Jasa Indonesia Cabang Pekanbaru - Qomariah Lahamid; Hafizah Indriyanti (Pelantar Press, 2021)
This study aims to determine the sales strategy carried out by PT. Pekanbaru Indonesia Services Insurance Branch. This research is a qualitative descriptive study. The data used in this language are secondary and primary data. The informants in this study were the leadership and marketing division of PT. Insurance Services Indonesia Pekanbaru Branch. The results showed that there are several sales strategies implemented by the company, namely E-Commerce, direct selling, selling and marketing by telephone, company referrals, and mail orders. The suggestion from this research is that it is necessary to improve the promotion strategy through brochures, advertisements, TV shopping and others, so that the public can see Jasindo's insurance products, including fire insurance. Then, further improve service to customers.